Efektivitas Manajemen Pendidikan dan Pelatihan Guru Berbasis Kompetensi di Balai Besar Pengembangan dan Penjaminan Mutu Pendidikan Vokasi Bidang Bangunan dan Listrik (BBPPMPV BBL) - Yovani Rahmita Simatupang; Sri Nurabdiah Pratiwi; Indra Prasetia (UMSU, 2023)
The purpose of this study is to find out and analyze: (1) the effectiveness of management of competency-based teacher education and training studied through the implementation of management functions which are planning, implementing, controlling and evaluating, and (2) the effectiveness as measured by Kirkpatrik’s Reaction and Learning Level. This study uses a combination methods of concurrent embedded with qualitative methods as the primary method. Concurrent embedded design is a research method that combines qualitative and quantitative research methods by mixing the two methods unequally. The research begins by collecting qualitative data and at the end of the research is supported by quantitative descriptive using average data and percentage levels. Quantitative descriptive data obtained by using a questionnaire. The research was conducted at the Center for Development and Quality Assurance for Vocational Education in the Field of Building and Electrical (BBPPMPV BBL) Medan. Primary data comes from interviews with 11 management elements of BBPPMPV BBL Medan and widyaiswara (trainer) and questionnaires to 85 teachers who are training participants of 6 training titles in the Electricity Expertise Program. The results of the research findings showed that education and training management had been carried out effectively. This is proven based on interviews and observations that the planning, implementation, control and evaluation of education and training are carried out well and in accordance with the education and training management theory put forward by Notoatmodjo (2011), Risdiyati (2012) and P.Siagian (1985). The results of the questionnaire also show that the education and training program is running effectively where: (1) evaluation results based on reactions show that 60.74% of training participants stated that they were satisfied and very satisfied with the implementation of the training, and (2) evaluation results based on learning levels showed that there was an increase in knowledge an average of 32.14 points.